PENGEMBANGAN PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: STRATEGI TANTANGAN DAN SOLUSI - Zeni Nurjanah; Amelia Apriyani, Ranti Aprilia, Nurfitria (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Learning Indonesian at the elementary school level plays a very important role in forming the basis of students' language skills from an early age. In an increasingly globalised era, good language skills are not only necessary for communicating with others, but also for understanding and accessing various information. However, the process of learning Indonesian in elementary school often faces various challenges that hinder its eflectiveness. Some of the main challenges faced in learning Indonesian in elementary school include students' lack of interest and motivation towards language learning, limited use of varied and interesting teaching methods, and lack of support from the social environment and parents. Limited resources, such as inadequate textbooks and lack of access to educational technology, are also factors that complicate the learning of Indonesian in primary schools. To overcome these challenges, it is important to formulate innovative and eflective learning strategies. One strategy that can be applied is the use of an interactive and fun learning approach, where students are actively involved in the learning process. This can be done through the use of educational games, group discussions, and practical activities relevant to students' daily lives. In this way, it is hoped that students will be more interested and motivated to learn Indonesian. In addition, the use of technology in learning Indonesian is also a solution that needs attention. The use of language learning applications, educational videos, and online learning platforms can provide a more engaging and interactive learning experience, allowing students to learn in a more flexible way that suits their individual learning styles. Collaboration between schools, parents, and the community is also an important aspect of creating an environment that supports learning Indonesian. Schools can hold seminars or workshops for parents on the importance of their role in supporting children's language learning at home. Extracurricular activities, such as poetry reading competitions, storytelling, or drama, can also be used as a means of improving students' language skills while fostering a love of Indonesian language and literature. In this context, training for teachers to improve their pedagogical competence is also essential. Teachers who are skilled and creative in teaching will be able to provide a more meaningful learning experience for students. The development of a relevant and interesting curriculum, as well as the adaptation of teaching materials to the needs and interests of students, will greatly help in improving the eflectiveness of learning. By implementing these strategies and solutions, it is hoped that Indonesian language learning in elementary school will not only run smoothly, but will also have a significant positive impact on improving students' language skills. Through the joint eflorts of all parties involved, it is hoped that the younger generation can grow into individuals who not only have a good command of the Indonesian language, but also have a sense of pride in the nation's language and culture.